2019
DOI: 10.1186/s40364-019-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from mesenchymal stem/stromal cells: a new therapeutic paradigm

Abstract: Mesenchymal stem/stromal cells (MSCs) have been demonstrated to hold great potential for the treatment of several diseases. Their therapeutic effects are largely mediated by paracrine factors including exosomes, which are nanometer-sized membrane-bound vesicles with functions as mediators of cell-cell communication. MSCderived exosomes contain cytokines and growth factors, signaling lipids, mRNAs, and regulatory miRNAs. Increasing evidence suggests that MSC-derived exosomes might represent a novel cell-free th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
232
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(236 citation statements)
references
References 64 publications
3
232
0
1
Order By: Relevance
“…The absence of these proteins on the exosomal surface suggests no immune rejection can be expected for allogeneic therapeutics [32][33][34][35]. Exosomes derived from stem cells are actively being developed as a cell-free therapy because they recapitulate the functions of stem cells such as repair, regeneration, anti-inflation, and immune modulation without the limitations and risks of stem cells themselves [30,31,36,37]. As an example, exosomes derived from MSCs have therapeutic effects on various diseases including myocardial infarction [6,38], CCl4-induced liver injury [39], graft-versus-host disease (GvHD) [20], acute and chronic kidney injury [40], and atopic dermatitis [34,41].…”
Section: Exosomes and Extracellular Vesiclesmentioning
confidence: 99%
“…The absence of these proteins on the exosomal surface suggests no immune rejection can be expected for allogeneic therapeutics [32][33][34][35]. Exosomes derived from stem cells are actively being developed as a cell-free therapy because they recapitulate the functions of stem cells such as repair, regeneration, anti-inflation, and immune modulation without the limitations and risks of stem cells themselves [30,31,36,37]. As an example, exosomes derived from MSCs have therapeutic effects on various diseases including myocardial infarction [6,38], CCl4-induced liver injury [39], graft-versus-host disease (GvHD) [20], acute and chronic kidney injury [40], and atopic dermatitis [34,41].…”
Section: Exosomes and Extracellular Vesiclesmentioning
confidence: 99%
“…Accumulating evidence has strongly revealed that exosomes derived from stem cells are safe and effective for treating renal diseases in rat and mouse models [8,9]. Exosomes secreted by MSCs have a significant protective effect on renal injury in both acute kidney injury (AKI) and chronic kidney disease [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Current knowledge on mesenchymal stromal cells (MSCs) as future medicinal products in the field of regenerative medicine sheds light on the crucial role of their secreted factors and extracellular vesicles (EVs) to stimulate tissues and cells. In particular, by avoiding the concerns of using live and replicating cells that may undergo mal-differentiation or mutation, the idea of EVs as therapeutics is being explored, since they can mimic several biological actions of MSCs [1] through embedded lipids, proteins, mRNAs and miRNAs [2,3], therefore acting as biological nanocarriers. Even more intriguing, MSC-EVs may be engineered by either exogenous load [4] or reprogramming of the secreting cells [5,6] to shuttle and deliver specific and therapeutic molecules, such as miRNAs or mRNAs, eventually driving the focused influence on target cells [7].…”
Section: Introductionmentioning
confidence: 99%